Analogies to demonstrate the effect of roughness on surface wettability. (2nd October 2017) - Yolcu, Hasan
ABSTRACT: This article presents an analogy to illustrate the effect of surface roughness on surface wettability. I used a water-filled balloon to represent water droplet, a toothpick to represent surface roughness and Styrofoam as the surface. The analogies presented in this article will help visualize how roughness affects the wettability of the surface and therefore can be used to introduce surface wettability to high school students.